(untitled) (The South East European Journal of Economics and Business, 2019)
The phenomenon of pension funds industry growth in the last decades is inevitable in Central and Eastern European countries including Croatia that was enacted by the systemic pension reforms and introduction of mandatory private individual schemes. One of the main roles of the pension funds is to collect and invest the money contributed by the employer or the employee during working years until retirement. Therefore, development of pension funds as institutional investors is especially important for capital markets as well as for the whole economy. The aim of this paper is to examine performance of pension funds in Croatia, or more precisely, to measure the mandatory pension funds technical efficiency. By applying the methodology of data envelopment analysis on a sample of 12 mandatory pension funds for 2015-2018 period, we provide further evidence on their efficiency level. The results have shown very small differences among relative inefficient pension funds.